2014
DOI: 10.1007/s11258-014-0429-5
|View full text |Cite
|
Sign up to set email alerts
|

Linking patterns and processes through ecosystem engineering: effects of shrubs on microhabitat and water status of associated plants in the high tropical Andes

Abstract: 9Studies on alpine and semi-arid environments indicate that plants that act as ecosystem engineers improve 10 microhabitat conditions and modify local plant abundance and diversity. However, few studies have linked these 16show that H. laricifolium dampened temperature oscillations and increased soil water and organic matter contents, 17 the effect being more pronounced at the drier, lower elevation site. While positively associated forbs showed an 18 improvement in their water status when growing under the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 52 publications
3
36
0
Order By: Relevance
“…However, previous research [22, 23] proved that cushion plants create thermally-buffered habitat patches with higher humidity and lower temperature than surrounding open areas. Available data about soil beneath shrubs and tussocks showed marked differences in that below the tussock patches the temperature was lower than below shrubs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous research [22, 23] proved that cushion plants create thermally-buffered habitat patches with higher humidity and lower temperature than surrounding open areas. Available data about soil beneath shrubs and tussocks showed marked differences in that below the tussock patches the temperature was lower than below shrubs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies focused on alpine environments at inter-tropical latitudes, demonstrated how ecosystem engineers are capable of enhancing landscape-level richness by adding new species to the community through the regulation of temperature extremes and the modification of soil properties [22]. Moreover, they demonstrated how these nurse-induced microhabitat modifications positively influenced the physiological parameters of facilitated species [23]. However, other authors found contrasting results on the effect of ecosystem engineers on species richness at a wide scale [4].…”
Section: Introductionmentioning
confidence: 99%
“…; Ramírez et al. ). Plants may also exert a facilitation effect through other processes, such as litter accumulation (Facelli & Pickett ) or by attracting seed dispersing animals, reducing the effect that the distance to the forest edge has on dispersal (Duncan & Chapman ).…”
Section: Introductionmentioning
confidence: 98%
“…The facilitating species studied under the stress‐gradient hypothesis are commonly ecosystem engineers. For example, nurse plants shelter seedlings of other species from harsh conditions in the microclimate formed by their canopy, but in the absence of such stress the plants merely compete (Ramírez, Rada, & Llambí, ). There has been increased effort to investigate the applicability of the stress‐gradient hypothesis to species other than plants (Bakker, Dobrescu, Straile, & Holmgren, ; Dangles, Herrera, & Anthelme, ; Fugère et al, ).…”
Section: Introductionmentioning
confidence: 99%